Tracking the Path of Communities of Inquiry in TEFL: A Literature Review - Darlene González Miy; Luz Edith Herrera Díaz (HOW, 2015)
The community of inquiry is a techno-pedagogical framework that has gathered significant attention in online education research. It has been implemented in diverse disciplines, (foreign) language learning being one of particular interest for the authors of this paper. Due to the dynamics proposed by the framework, it appears as a practical and relevant option to generate a successful learning experience for English as a Second or Foreign Language learners. Therefore, this article provides a brief description of the model, its theoretical foundation, its applications and potential uses in the area of language learning in online environments.